Effect of Age, Gender, And BMI on the Incidence and Satisfaction of A Popeye Deformity Following Biceps Tenotomy or Tenodesis: Outcomes of A Multicenter Randomized Controlled Trial. Issue 7 (30th July 2021) - Woodmass, Jarret; McRae, Sheila; Sasyniuk, Treny; Lapner, Peter; MacDonald, Peter
Objectives: The purpose of this study was to 1) determine the rates of popeye deformity following biceps tenotomy versus tenodesis 2) identify predictors for developing a deformity, and 3) report the subjective and objective outcomes in patients with a popeye deformity. Methods: Data for this study were collected as part of a randomized clinical trial comparing tenodesis versus tenotomy in the treatment of lesions of the long head of biceps tendon. Patients 18 years of age or older undergoing arthroscopic shoulder surgery with intraoperative confirmation of a lesion of the long head of the biceps tendon randomized to one of these techniques were included. The primary outcome measure for this sub-study was the rate of a popeye deformity at 24-months post-operative as determined by an evaluator blinded to group allocation. Secondary outcomes were presence/absence of a popeye deformity based on patients responding to the following question: "Do you notice a bulge on the front of your upper arm above your elbow?" If yes, patients indicated their satisfaction with the appearance of their arm on a 10 cm visual analog scale (VAS) with 0="Unsatisfactory" and 10="Satisfactory" as the anchors. Patients were also asked to indicate if they experienced pain or cramping on a VAS, and complete the American Shoulder and Elbow Score (ASES) and the Western Ontario Rotator Cuff score (WORC). Isometric elbow flexion and supination strength (ratio of affected and unaffected) were also measured. Kappa was calculated to measure interrater reliability between patient and evaluator on the presence of a deformity, and logistic regression was used to identify possible predictors of its occurrence. Pearson correlations were performed to identify factors associated with dissatisfaction in appearance. Results: Fifty-seven participants were randomly assigned to each group of which 42 in the tenodesis group and 45 in the tenotomy group completed a 24-month follow-up. The overall incidence of popeye deformity based on clinical assessment was 21%, 9.5% (4/42) in the tenodesis group and 33% (15/45) in the tenotomy group. The odds of a popeye deformity resulting from a tenotomy was 4.3 times that of tenodesis (OR 4.3, 95% CI: 1.25-14.76; p=0.018). Gender was tending towards significance with males having 7.3 greater odds of a perceived deformity (p=0.067), while age and BMI were not predictive. There were no differences between those with and without a perceived deformity with respect to subjective and functional outcome measures. Based on patient self-assessment, the overall incidence of a deformity was 18%, 25% in the tenotomy group and 10% in the tenodesis group. The odds of a patient reporting a popeye deformity following tenotomy was 3.66 relative to tenodesis (OR=3.66, CI 95% 1.08-12.44; p=0.038). Gender, BMI, and age were not predictive of self-report of a popeye. Those with and without a self-reported popeye deformity differed with respect to pain (p=0.001), cramping (0.039), and WORC scores (p<0.006), there was no difference in ASES or elbow strength. Of those who reported having a deformity, mean (SD) satisfaction score reported on the appearance of their arm was 7.3 (2.6). Increasing satisfaction score was significantly correlated with increasing patient age (r=0.640; p=0.025) but there was no association with gender or BMI. Inter-rater agreement between clinical assessment and self-reported popeye deformity was substantial with a kappa of 0.635 (p<0.001). However, 8% (7/87) of patients with a popeye deformity did not perceive it and 3% (3/87) of patients reported a popeye deformity that was not detected by the clinical assessor. Conclusions: The odds of observing a popeye deformity based on clinical assessment following tenotomy was 4.3 times higher than tenodesis at 24-months post-operative. Male gender may contribute to increased incidence, while age and BMI were not major contributors to the presence/absence of a popeye. In patients who reported a popeye deformity, increasing age was associated with increased satisfaction in the appearance of the arm.